(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
This research gives a description of an ultrasonic mechatronic system block diagram and justifies the necessity to control the acoustic field in the system. Such a control can be exercised by changing the vibration parameters of the piezoelectric emitter working surface. Therefore the piezoelectric emitter is considered as a link in the system of the automatic control. Possibility to use their transitions functions was experimentally proved. Conclusions were made regarding the introduction to a feedback system considering the parameters of the acoustic field